The resources-economy slugs production technology for production of instrument - T. M. Titova; A. P Ogurtsov; V. V. Lunev; G. A. Bjalik; S. A. Adamchuk (Литьë и металлургия)
Deficiency and high cost of alloying elements, used in production of high-speed steel, stipulate expediency of searching of the efficient resources-economy production technologies of laminar slugs, meant for the production of instrument.